1985
DOI: 10.1051/agro:19850708
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité naturelle des souches du virus Y de la pomme de terre dans les cultures de piment du sud-est de la France. Caractérisation et classification en pathotypes

Abstract: RÉSUMÉ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 0 publications
2
40
0
1
Order By: Relevance
“…Based on the phenotypic response of a differential pepper host range, strains of PVY have been grouped according to virulence and three pathotypes have been defined (Gebre Selassie et al ., 1985) : P(0), the common pathotype is virulent on Yolo Wonder ; the P(1) pathotype is virulent on Yolo Y ; the P(1,2) pathotype is virulent on Yolo Y and Florida VR2 . These different strains are very closely related serologically (Gebre Selassie et al ., 1985) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the phenotypic response of a differential pepper host range, strains of PVY have been grouped according to virulence and three pathotypes have been defined (Gebre Selassie et al ., 1985) : P(0), the common pathotype is virulent on Yolo Wonder ; the P(1) pathotype is virulent on Yolo Y ; the P(1,2) pathotype is virulent on Yolo Y and Florida VR2 . These different strains are very closely related serologically (Gebre Selassie et al ., 1985) .…”
Section: Introductionmentioning
confidence: 99%
“…These different strains are very closely related serologically (Gebre Selassie et al ., 1985) . PVY isolates collected from pepper plants and weeds in France, Italy, and Spain mostly belonged to the P(0) pathotype and incited severe necrotic symptoms on the cultivar, Bastidon (Marte et al ., 1991 ;Arteaga & Ortega, 1986) .…”
Section: Introductionmentioning
confidence: 99%
“…PVY N and PVY O isolates from potato do not infect pepper mechanically (Gebre Selassie et al, 1985) but this assay has not previously been reported for PVY C isolates. Results obtained in the host range assay are presented in Table 1 : PVY C isolates 26, 28 and 29 infected pepper as efficiently as did PVY-P21.…”
Section: Cadimentioning
confidence: 71%
“…Thus, the ability or inability to infect pepper turned out to be a PVY C strain-specific property. Interestingly, the PVY C isolates of the PVY NP cluster (PVY C" ) were able to infect pepper while other potato isolates are not (Gebre Selassie et al, 1985). This could imply some type of coevolution within PVY and its plant hosts, as suggested for the Potyviridae in general (Ward et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation